Skilled Birth Attendance and Quality of Life among Young Mothers in Eastern Uganda: Evidence from a Cross-Sectional Study - Nakkazi Joan; Odoki Martin; Frank Pio Kiyingi; Miisa Nanyingi; Miph Musoke (International Journal of Global Health, 2026)
Introduction Skilled birth attendance (SBA) is a proven intervention for reducing maternal and newborn morbidity and mortality through the prevention and management of childbirth complications. While its survival benefits are well established, less is known about its association with health-related quality of life (HRQoL), an important indicator of women’s physical, psychosocial and social well-being. Evidence on this relationship remains limited among young mothers in low resource settings such as Uganda. This study examined the association between SBA and HRQoL among young mothers aged 10-24years in Eastern Uganda. Methods A cross-sectional study was conducted among 967 young mothers in Kamuli, Pallisa, and Ngora districts. Participants were young mothers aged 10–24 years who had delivered within the previous two years. Data were collected using structured interviewer-administered questionnaires. HRQoL was assessed using the WHOQOL-BREF tool on a five-category self-rated scale. Descriptive statistics summarized participant characteristics, chi-square tests and One way ANOVA explored bivariate associations, and ordered logistic regression estimated the relationship between SBA and HRQoL. Skilled birth attendance was defined as delivery assisted by a trained and accredited health professional (doctor, nurse or midwife) in accordance with WHO recommendations. Results Most respondents were aged 18–24 years (91.3%), married (75.8%), and had prior pregnancy experience (90.4%). Bivariate analysis demonstrated that skilled birth attendance (SBA) utilization was significantly associated with several key factors, including age (χ²(1)=5.75, p=0.017), religion (χ²(1)=18.09, p<0.001), knowledge of maternal healthcare services (χ²(1)=26.84, p<0.001), seeking care immediately (χ²(1)=38.82, p<0.001), perceived quality of care (χ²(3)=71.90, p<0.001), and previous pregnancy complications (χ²(1)=6.91, p=0.009). These findings indicate that younger mothers, those lacking awareness, and those reporting poorer care experiences were less likely to deliver with assistance of skilled birth attendant. An ordered logistic regression analysis further established that utilization of SBA was a significant predictor of health-related quality of life (HRQoL) (z = 4.12, p < 0.001). Young mothers who delivered with the assistance of a skilled birth attendant had significantly higher odds of reporting better HRQoL compared to those who did not (OR = 1.761, 95% CI 1.345 2.306), implying that SBA users were approximately 1.76 times more likely to fall into a higher HRQoL category. The overall model was statistically significant (LR χ² (1) = 17.01, p < 0.001), although the pseudo-R² of 0.006 suggests limited explanatory power. Nonetheless, the findings highlight the independent contribution of SBA to improved maternal well-being, underscoring its importance in enhancing quality of life among young mothers. Conclusion Skilled birth attendance was positively associated with better HRQoL among young mothers in Eastern Uganda. Expanding equitable access to skilled delivery care may enhance physical safety, emotional well-being, and overall quality of life for this vulnerable population.
Keywords: Skilled birth attendance